2021
DOI: 10.1016/j.isci.2020.101960
|View full text |Cite
|
Sign up to set email alerts
|

Human and mouse PD-L1: similar molecular structure, but different druggability profiles

Abstract: In the development of PD-L1-blocking therapeutics, it is essential to transfer initial in vitro findings into proper in vivo animal models. Classical immunocompetent mice are attractive due to high accessibility and low experimental costs. However, it is unknown whether inter-species differences in PD-L1 sequence and structure would allow for human-mouse cross applications. Here, we disclose the first structure of the mouse (m) PD-L1 and analyze its similarity to the human (h) PD-L1. We show that mPD-L1 intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
59
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 50 publications
9
59
1
Order By: Relevance
“…Durvalumab blocks the human PD-L1 but not the mouse PD-L1 protein, as we have shown in our recent manuscript [36]. In our hands, none of the small molecules and macrocyclic peptides tested in our laboratory were able to bind to mouse PD-L1, as we have verified either with the NMR study or the hybrid, mPD-L1/hPD-1 ICB assay [36]. Importantly, similar observations have been reported by others.…”
Section: Specificity Towards the Human And Mouse Pd-l1supporting
confidence: 89%
See 2 more Smart Citations
“…Durvalumab blocks the human PD-L1 but not the mouse PD-L1 protein, as we have shown in our recent manuscript [36]. In our hands, none of the small molecules and macrocyclic peptides tested in our laboratory were able to bind to mouse PD-L1, as we have verified either with the NMR study or the hybrid, mPD-L1/hPD-1 ICB assay [36]. Importantly, similar observations have been reported by others.…”
Section: Specificity Towards the Human And Mouse Pd-l1supporting
confidence: 89%
“…Out of the tested therapeutic antibodies, atezolizumab blocks both human and mouse PD-L1 (mPD-L1). Durvalumab blocks the human PD-L1 but not the mouse PD-L1 protein, as we have shown in our recent manuscript [36]. In our hands, none of the small molecules and macrocyclic peptides tested in our laboratory were able to bind to mouse PD-L1, as we have verified either with the NMR study or the hybrid, mPD-L1/hPD-1 ICB assay [36].…”
Section: Specificity Towards the Human And Mouse Pd-l1supporting
confidence: 75%
See 1 more Smart Citation
“…The results are, therefore, consistent with our previous studies, in which we showed that the biphenyl moiety from anti-PD-L1 inhibitors binds to human PD-L1 and not to the murine analogue. 31 …”
Section: Results and Discussionmentioning
confidence: 99%
“…The humanized immune checkpoint mice are carefully designed as immuno-oncology mouse models for reliable in vivo evaluation and validation of checkpoint blockers drugs and their combination with other antitumor drugs ( 29 ). According to previous studies, although there are structural similarities between human and mouse PD-L1 proteins, there are significant differences in the druggability of these two proteins ( 30 ). In line with reported results, our study showed that small molecules, peptides, and some human anti-PD-L1 antibodies bound to human PD-L1, but not to mouse PD-L1.…”
Section: Discussionmentioning
confidence: 99%